Comparison of Stress Coping Styles Between Mental Health Technicians and Psychiatric Nurses Working in a Tertiary Care Psychiatric Hospital - Hussain, Muhammad Ibrar; Ali, Sohail; Malik, Muhammad Sheraz; Ullah, Ata; Imtiaz, Nomita; Irshad, Sonia (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the stress coping styles between mental health technicians and psychiatric nurses working in tertiary care psychiatric facility.Study Design: cross-sectional study.Place and Duration of Study: Armed Forces Institute of Mental Health (AFIMH), Rawalpindi and Combined Military Hospital, Lahore, Pakistan, from Oct 2023 to Mar 2024.Methodology: A total of 120 mental health workers who were working in two tertiary care psychiatric facilities were included in the study. Stress coping strategies were assessed by using “Brief COPE inventory” which is a 28-item self-report questionnaire used in psychiatric and medical settings to assess the coping strategies individuals employ to manage stress. The inventory was employed in Urdu Version to facilitate participants.Results: Among mental health technicians, 38.3% hailed from urban locales, while 61.7% originated from rural areas. Conversely, the majority of female psychiatric nurses, totaling 95.0%, hailed from urban environments, with only 5.0% originating from rural settings. Coping strategies commonly employed by female psychiatric nurses included 62.0% problem focused coping, 26.0% emotional focused and 12.0% avoidance coping techniques while mental health technicians used included 67% problem focused coping, 13.0% emotional focused and 20.0% avoidance coping.Conclusion: Mental health technicians used more problem focused stress coping strategies as compared to female psychiatric nurses. Cognitive reshaping of female psychiatric nurses can be done in order to maximize their output.